Plant mediated synthesis of AgNPs and its applications: an overview. Issue 12 (29th September 2021) - Shyam, Aswathi; Chandran S., Smitha; George, Bini; E., Sreelekha
Abstract: Plant mediated synthesis of nanoparticles is a path breaking approach to fabricate ecologically friendly nanoparticles which can be utilized in various applications. The majority of the existing procedures used for nanoparticles synthesis rely up on chemical and physical methods, these methods are sometimes harmful and potentially dangerous to the environment and living organisms. But synthesis of nanoparticles in a green way using plant extract is a unique, systematic, affordable, and environmentally sound method for synthesizing nanoparticles with selective and specific properties and applications. In this article, the potential applications of plant mediated synthesized noble metal NPs, especially silver is discussed. It is astonishing to understand how a tiny particle is influencing our whole life and that's high lightened in this article. Graphical Abstract: UF0001